Morphology, resistivity and corrosion behavior of tin coatings plated from citric acid bath - Sharma, Ashutosh; Park, Young Min; Lee, Sangyeob; Ahn, Byungmin (Materials Research Express, 2019)
Pulse electrodeposition of Sn from an electrolyte containing stannous sulfate and citric acid was investigated. The corrosion investigations were done by electrochemical potentiodynamic polarization methods. The phase evolution and coating morphology were studied by x-ray diffraction experiment and scanning electron microscopy. All the deposited films exhibit tetragonal tin β-Sn structure. The coating microstructure consists of big sized grains at lower current density which are refined at higher current density. The electrical resistivity of the coatings was increased continuously with current density. The coatings show the best corrosion resistance at a current density of 30 mA cm-2. This study shows that developed coatings can be a potential candidate for Pb-free soldering technology.
Keywords: Coating microstructures; Coating morphology; Corrosion behavior; Electrochemical potentiodynamic polarization method; Lead-Free; Phase evolutions; Pulse electrodeposition; Soldering technology; citric acid; coating; lead-free; morphology; tin plating